1987
DOI: 10.1144/gsl.sp.1987.028.01.14
|View full text |Cite
|
Sign up to set email alerts
|

A physical model for Cenozoic extension of western North America

Abstract: We investigate the possibility that the onset and development of Cenozoic extension in western North America was governed by the potential energy contrast within, and mechanical properties of, lithosphere that was previously thickened during the Sevier and Laramide Orogenies. The strength of the lithosphere can be defined by its vertically averaged properties; to a first approximation, this strength is too great for geologically significant extension to occur unless the Moho temperature exceeds about 700~ (+ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
101
1
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(110 citation statements)
references
References 31 publications
5
101
1
3
Order By: Relevance
“…Sonder et al (1987) modelled these phenomena and concluded that a time delay of as much as 100 million years can occur between the end of compression and initiation of extension, depending on factors such as the thermal regime of the lithosphere and particularly the Moho temperature. For a relatively hot Moho temperature (500-7008C), the time delay is near zero.…”
Section: Previous Thoughts On Crustal Thickness Of the Great Basin Dumentioning
confidence: 99%
See 1 more Smart Citation
“…Sonder et al (1987) modelled these phenomena and concluded that a time delay of as much as 100 million years can occur between the end of compression and initiation of extension, depending on factors such as the thermal regime of the lithosphere and particularly the Moho temperature. For a relatively hot Moho temperature (500-7008C), the time delay is near zero.…”
Section: Previous Thoughts On Crustal Thickness Of the Great Basin Dumentioning
confidence: 99%
“…Sonder et al 1987). Parcels of partial melt too small in concentration to form buoyant diapirs can nonetheless mix with ascending mantle-derived magmas.…”
Section: Ba and Rbmentioning
confidence: 99%
“…In Tibet as well as in the Basin and Range Province of the western USA, it has been argued that present-day crustal flow is strongly influenced by forces induced by large gradients in gravitational potential energy (England & Molnar 1997;Jones et al 1996;Flesch et al 2000). A warmer geotherm reduces the strength of the continental lithosphere and, as a rule of thumb, it is inferred that a thickened continental crust spreads under its own weight (i.e., Argand Ratio !1 for a given effective strain rate) when the temperature at the Moho is above c. 7008C (e.g., Sonder et al 1987).…”
mentioning
confidence: 99%
“…These include (1) extension, has been proposed by several authors [e.g., Coney and Harms, 1984;Mayer, 1986;Holt et al, 1986;Sonder et al, 1987;Dewey, 1988]. Subsequent extension may return the crust in these regions to an "average" crustal thickness.…”
mentioning
confidence: 99%